Designing agricultural marketing systems in developing countries - Shaffer, James D. (East Lansing, Michigan: Michigan State University, 1972)
The paper aims at discussing the design of improved agricultural marketing systems as a means of stimulating economic development.
rpm 31/01/2019
Loans
Keywords: Agriculture; Marketing; Developing Countries